External sovereign debt in a monetary union: Bailouts and the role of corruption - Carolina Achury; Christos Koulovatianos; John D. Tsoukalas (Center for Economic Studies and ifo Institute (CESifo), 2011)
We build a tractable stylized model of external sovereign debt and endogenous international interest rates. In corrupt economies with rent-seeking groups stealing public resources, a politico-economic equilibrium is characterized by permanent fiscal impatience which leads to excessive issuing of sovereign bonds. External creditors envision the corrupt economy's fiscal impatience and buy its bonds at higher interest rates. In turn, this interest-rate increase exacerbates the problem of oversupplying debt, leading the economy to a perfect-foresight trap. In incorrupt countries which have entered a high-interest-rate/high debt-GDP-ratio trap because an immediately recent disaster has caused a sudden jump to a high outstanding debt-GDP ratio, we show that bailout plans with controlled interest rates can help in reducing debt-GDP ratios after some time. On the contrary, under corruption, we show that bailouts are ineffective unless rent-seeking groups are eradicated.
Keywords: H63; F34; F36; G01; E44; E43; D72; 330; sovereign debt; world interest rates; international lending; rent seeking; Öffentliche Schulden; Auslandsverschuldung; Währungsunion; Rent Seeking; Korruption; Zins; Schuldenübernahme; Theorie